P03.16 Sexual abuse reported by young australian women. (13th September 2015) - Garland, SM; Jayasinghe, Y; Callegari, ET; Gorelik, A; Subasinghe, AK; Wark, JD
Abstract : Introduction: Young women are under-represented in health research despite their transitioning a life stage critical for future health outcomes. Sexual abuse has become a critical issue, globally, leading to significant long term morbidity. We investigated the prevalence of unwanted sexual experiences (USEs) in young women, residing in Victoria, Australia. Methods: The Young Female Health Initiative (YFHI) and Safe-D are comprehensive studies of physical, sexual, reproductive, and mental health of young females. Participants (aged 16–25 years) are recruited through Facebook. Consenting participants complete an extensive online health survey and attend a site visit. USEs are assessed using questionnaires and a protocol for protection of participants developed to ensure their safety. Results: Data available for 398 participants (YFHI: N = 178; Safe-D: N = 220) shows 14% recalled a USE when they were < 16 years of age, of whom, 62% indicated they suffered from depression, 32% reported penile-genital contact, and 20% had been diagnosed by a doctor or health professional with a sexually transmitted infection. In women who recalled a USE between 16–18 years of age (60/398, 15%), 42% stated they felt pressured into sexual intercourse with a man, and 28% reported having been raped. In women aged ≥18 years, no significant differences were observed between the proportion of women from the YFHI study, who reported a USE at < 16 years of age (19%), compared to participants from the Safe-D study (11%,  p > 0.05). Conclusion: To our knowledge this is the first Australian study in which the prevalence of USE in women as young as 16 years has been assessed. Prevalence was lesser than in other Australian community studies (25–30%). This may be related to age or reluctance to disclose. USEs should be researched further in this population, to develop intervention strategies. Disclosure of interest statement: Nil.